2006
DOI: 10.3390/i7050130
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 2,2-Diphenyl-1-picrylhydrazyl with HO•, O2•–, HO– ,and HOO– Radicals and Anions

Abstract: Using electronic absorption spectra and thin layer chromatography, the reaction of 2,2-diphenyl-1-picrylhydrazyl (DPPH) with O 2•-, HO • , HO -, and HOO -anions and free radicals revealed the formation of the para-nitro-and para-hydroxy-derivatives of 2,2-diphenyl-1-picrylhydrazine (DPPH-H) and of DPPH fragmentation products (diphenylamine, tetraphenylhydrazine). The reaction of DPPH with the O 2 •-anion-radical (from KO 2 in benzene solution at room temperature in the presence of 18-crown-6 ether) is pseudo-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…This seems to be in consonance with higher phytochemical content in aqueous leaf fraction than the hexane leaf fraction. DPPH radicals had shown that it react with appropriate reducing agent with concomitant stoichiometric color loss depending on the number of electrons taken up [34]. Furthermore, previous study had shown that most antioxidant compounds are structurally polar.…”
Section: Resultsmentioning
confidence: 99%
“…This seems to be in consonance with higher phytochemical content in aqueous leaf fraction than the hexane leaf fraction. DPPH radicals had shown that it react with appropriate reducing agent with concomitant stoichiometric color loss depending on the number of electrons taken up [34]. Furthermore, previous study had shown that most antioxidant compounds are structurally polar.…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48][49][50][51] It is known that DPPH undergoes acid-base reactions with anions to yield the DPPH -anion [16][17][18]32,33,38] (Scheme 2). In a study of the reaction of the above supramolecular complex 12 with DPPH (in molar ratio 3/DPPH 1:2.5) in dichloromethane at room temperature, the process was monitored (Scheme 6) by electronic absorption spectroscopy for DPPH -(as supramolecular complex 13) with λ max = 428 nm, [16][17][18]52] and by TLC after operations (ii) and (iii) (for 5 converted into 1 and DPPH -converted into DPPH-H). During the first 30 min, the spectrophotometric analysis showed the presence of the DPPH -anion (as supramolecular complex 13) also confirmed by TLC (as DPPH-H), www.eurjoc.orgsyringaldehyde (1) (Scheme 6), and other minor TLC spots.…”
Section: The Reaction Of Dpph With the Sodium Aroxide 3 In The Presenmentioning
confidence: 99%
“…[6,[10][11][12][13][14][15][16][17][18] In the latter reaction, DPPH becomes reduced to the corresponding hydrazine (DPPH-H, Scheme 2) or, in alkaline medium, to the anion (DPPH -, Scheme 2). Depending on the reaction conditions, one or both phenyl groups of DPPH may become nitrated in their para positions; with one such para-nitro group one obtains compounds O 2 NDPPH, O 2 NDPPH-H, and O 2 NDPPH -, and with two such para-nitro groups one has compounds (O 2 N) 2 DPPH, (O 2 N) 2 DPPH-H, and (O 2 N) 2 -DPPH -(Scheme 2) [16,17,[24][25][26][27][28][29][30][31][32][33] . The reaction mechanism depends on the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…330 nm line is due to its reduced form DPPH H [7]. The DPPH • concentration evaluated on the basis of the absorbance at 520 nm is [DPPH • ] = (3.5 ± 0.5) × 10 ⎯5 mol/L (ε = 10 4 mol L -1 cm -1 [8]). In the case of mixing with water irradiated for 20 min, the intensity of the 520 nm line is much lower (curve 2) and the absorbance at 330 nm remains unchanged.…”
Section: Resultsmentioning
confidence: 99%